ACTIVITIES OF THE RUSSIAN-ASIAN BANK BRANCH IN TURKESTAN AT THE END OF THE 19TH AND THE BEGINNING OF THE 20TH CENTURY (Scientific journal of the Fergana State University, 2024)
The purpose of the research is to analyse the activities of the Russian-Asian Bank branch in Turkestan in the late 19th and early 20th century in order to identify the influence of the banking sector on the economic development of the region. banking sector on the economic development of the region. The objectives of the work include study of the main stages of formation and functioning of the bank in the context of historical and economic changes in the region, identification of key areas of banking activities and their impact on the local economy. The methodological approach includes the analysis of statistical data and historical literature to build a comprehensive understanding of the role and influence of the Russian-Asian Bank in Turkestan. The results The results of the study will include a detailed description of the specifics of the bank's activities, its contribution to the development of the industrial and financial sectors, as well as a generalisation of the bank's influence on the social and economic development of Turkestan. as well as a generalisation of the bank's influence on the socio-economic situation in the region. The conclusion will be aimed at highlighting the main conclusions and practical recommendations for a better understanding of the role of banking capital in the historical perspective and the possible impact of the bank on the socio-economic situation in the region. capital in a historical perspective and the possible application of this knowledge in a contemporary context.